Polarizable Atomic Multipole Water Model for Molecular Mechanics Simulation - Ren, Pengyu; Ponder, Jay W (The journal of physical chemistry. B, 2003)
A new classical empirical potential is proposed for water. The model uses a polarizable atomic multipole description of electrostatic interactions. Multipoles through the quadrupole are assigned to each atomic center based on a distributed multipole analysis (DMA) derived from large basis set molecular orbital calculations on the water monomer. Polarization is treated via self-consistent induced atomic dipoles. A modified version of Thole's interaction model is used to damp induction at short range. Repulsion−dispersion (vdW) effects are computed from a buffered 14−7 potential. In a departure from most current water potentials, we find that significant vdW parameters are necessary on hydrogen as well as oxygen. The new potential is fully flexible and has been tested versus a variety of experimental data and quantum calculations for small clusters, liquid water, and ice. Overall, excellent agreement with experimental and high level ab initio results is obtained for numerous properties, including cluster structures and energetics and bulk thermodynamic and structural measures. The parametrization scheme described here is easily extended to other molecular systems, and the resulting water potential should provide a useful explicit solvent model for organic solutes and biopolymer modeling.